2022
DOI: 10.3389/fgene.2022.901838
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization and Comprehensive Analysis of NAC Transcription Factor Family in Nelumbo nucifera

Abstract: NAC (NAM, ATAF, and CUC) is a ubiquitously expressed plant-specific transcription factor (TF) family which is involved in the regulation of various biological processes. However, a systematic characterization of NAC gene family is yet to be reported in lotus. Here, 82 NnNAC genes which included five predicted membrane-bound NAC proteins were identified in the lotus genome. Phylogenetic analysis revealed seven-subfamily clusters (I–VII) of NnNAC proteins, with homologous gene pairs displaying similar conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…The number of introns in the KoNAC genes varied from 1 to 7, similar to numbers reported in many plant species ( Liu et al., 2019 ; Shan et al., 2020 ; Song et al., 2022 ). In general, the deletion or insertion of introns can result in a loss of gene function.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The number of introns in the KoNAC genes varied from 1 to 7, similar to numbers reported in many plant species ( Liu et al., 2019 ; Shan et al., 2020 ; Song et al., 2022 ). In general, the deletion or insertion of introns can result in a loss of gene function.…”
Section: Discussionsupporting
confidence: 80%
“…Many studies have been conducted to clarify the function of NAC TFs in reactions to various environmental stresses, such as salinity, drought, heat and flooding ( Fang et al., 2015 ; Yuan et al., 2020 ; Song et al., 2022 ). In the present study, the average expression level of the KoNACs was highest in roots, and a large number of KoNAC genes showed high levels of expression, such as KoNAC25 , KoNAC33 , KoNAC36 , KoNAC64 , KoNAC67 , KoNAC70 , KoNAC71 , and KoNAC75 ( Figure 8B ).…”
Section: Discussionmentioning
confidence: 99%
“…However, functional research of lotus NAC genes has rarely been reported. Eighty-two NAC genes were obtained using the website PlantTFDB, and we studied their potential functions in lotus seeds and response to complete submergence [ 61 ]. Compared to NAC genes of other plants, the number NAC genes in lotus root still needs to be found.…”
Section: Discussionmentioning
confidence: 99%
“…At present, more data on NAC transcription factors of plants have been collected from studies based on plant genomics [ 24 , 25 ] and bioinformatics [ 26 ]. Moreover, NAC transcription factors have promising applications in plant molecular breeding.…”
Section: Introductionmentioning
confidence: 99%